The Dialogue of Multicultural Education and Harmony in Prosperity Based on the Qur’an - Muhammad Yusuf; Achmad Abubakar; Mardan Mardan; Nahdhiyah Nahdhiyah; Abd Rahim (International Journal on Advanced Science, Education, and Religion, 2020)
This research aims to explore multicultural education dialogue and harmony in diversity based on the Qur'an. It aims to get anxious answers to various interpretations of the Qur'an, which then aims at understanding that is inclusive of the Qur'an. By conducting a thematic interpretation study with an anthropological approach, the concept of interpretation is found, which produces an inclusive understanding. It accepts diversity as sunnatullah by always maintaining tolerance and harmony in diversity. There are many Qur'anic verses which show that diversity is God's will as a test for humans to compete in goodness. Humans must realize tolerance, harmony, and cooperation, so it is necessary to form a collective agreement jointly. Therefore cross-faith and cultural dialogue must be carried out continuously by promoting ethics. Keywords: Multicultural Education, Anthropological, Diversity, Harmony